South African Women Leading Rural Schools During the COVID-19 Pandemic: Challenges and Resilience - Nkosi , Thembi; Moyo, Zvisinei (Journal of Education and Educational Development, 2023)
Since the arrival of COVID-19, schools have been confronted with complex problems, and the burden on women principals in rural schools has been enormous. - The COVID-19 pandemic has significantly increased the workload of women principals, affecting both their work and home life." This study sought to explore how the leadership roles of female principals in rural primary schools have been influenced during the COVID-19 pandemic. This qualitative study focused on women principals leading rural primary schools in South Africa during the COVID-19 pandemic, utilizing critical feminist theory for analysis. The study collected data through semi-structured interviews and document analysis. Women principals’ leadership was impacted by a lack of trust, insufficient resources and resistance presented by parents, teachers, and staff members directly and negatively affected the women principals and became an obstacle in pursuing their duties. - The shortage of infrastructure caused learners to attend school intermittently due to new timetabling models introduced to accommodate social distancing. The absence of e-learning amenities made it difficult for rural learners to receive education."The absence of e-learning amenities made it difficult for the rural learners to receive education. Further and future research should be conducted in other provinces to compare the experiences of female principals.
Keywords: COVID-19; women principals; rural areas; critical feminist theory; empathy; assertiveness; self-directed learning